Public Sentiment Analysis Towards Pertamina Using Naive Bayes and SVM Algorithms - Rendi Eko Kurniawan; Anindhita Rahmadini; Harun Al Rosyid (2025)
Abstract - The rapid spread of information through digital platforms has made public sentiment an important indicator for evaluating the credibility and performance of companies, including Pertamina. Several cases involving Pertamina throughout 2025 have triggered a surge of public responses on YouTube, which can be analyzed to understand patterns of opinion toward the corporation. This study aims to compare the performance of the Naive Bayes and Support Vector Machine (SVM) algorithms in classifying public sentiment into positive, neutral, and negative categories. A total of 33.221 YouTube comments were collected through a crawling process using the YouTube API, then processed through text preprocessing and TF-IDF weighting before being classified. The evaluation results show that Naive Bayes achieves an accuracy of 66%, with very high recall in the negative class but poor performance in the neutral and positive classes. Meanwhile, SVM achieves a higher accuracy of 77% with more balanced precision, recall, and F1-Score across all sentiment categories. Based on these results, SVM is proven to be more effective and reliable for sentiment analysis on unbalanced textual data related to Pertamina. The findings of this study are expected to support Pertamina in understanding public perception and improving decision-making related to service quality and corporate communication strategies.Keywords: Sentiment Analysis; Pertamina; YouTube; Naive Bayes; SVM; Abstrak - Pesatnya penyebaran informasi melalui platform digital menjadikan sentimen publik sebagai indikator penting untuk mengevaluasi kredibilitas dan kinerja perusahaan, termasuk Pertamina. Beberapa kasus yang melibatkan Pertamina sepanjang tahun 2025 telah memicu lonjakan respon publik di YouTube, yang dapat dianalisis untuk memahami pola opini terhadap korporasi. Penelitian ini bertujuan untuk membandingkan kinerja algoritma Naive Bayes dan Support Vector Machine (SVM) dalam mengklasifikasikan sentimen publik ke dalam kategori positif, netral, dan negatif. Sebanyak 33.221 komentar YouTube dikumpulkan melalui proses crawling menggunakan YouTube API, kemudian diproses melalui pra- pemrosesan teks dan pembobotan TF-IDF sebelum diklasifikasikan. Hasil evaluasi menunjukkan bahwa Naive Bayes mencapai akurasi 66%, dengan ingatan yang sangat tinggi di kelas negatif tetapi kinerja yang buruk di kelas netral dan positif. Sementara itu, SVM mencapai akurasi yang lebih tinggi sebesar 77% dengan presisi, ingatan, dan F1-Score yang lebih seimbang di semua kategori sentimen. Berdasarkan hasil tersebut, SVM terbukti lebih efektif dan handal untuk analisis sentimen terhadap data tekstual yang tidak seimbang terkait Pertamina. Temuan penelitian ini diharapkan dapat mendukung Pertamina dalam memahami persepsi publik dan meningkatkan pengambilan keputusan terkait kualitas layanan dan strategi komunikasi perusahaan.Kata kunci: Analisis Sentimen; Pertamina; YouTube; Naive Baye; SVM;